Decreased prevalence of Plasmodium falciparum resistance markers to amodiaquine despite its wide scale use as ACT partner drug in Zanzibar - Froberg, Gabrielle (2012)
Background: Zanzibar has recently undergone a rapid decline in Plasmodium falciparum transmission following combined malaria control interventions with artemisinin-based combination therapy (ACT) and integrated vector control. Artesunate-amodiaquine (ASAQ) was implemented as first-line treatment for uncomplicated P. falciparum malaria in Zanzibar in 2003. Resistance to amodiaquine has been associated with the single nucleotide polymorphism (SNP) alleles pfcrt 76T, pfmdr1 86Y, 184Y and 1246Y. An accumulation of these SNP alleles in the parasite population over time might threaten ASAQ efficacy. The aim of this study was to assess whether prolonged use of ASAQ as first-line anti-malarial treatment selects for P. falciparum SNPs associated with resistance to the ACT partner drug amodiaquine. Methods: The individual as well as the combined SNP allele prevalence were compared in pre-treatment blood samples from patients with uncomplicated P. falciparum malaria enrolled in clinical trials conducted just prior to the introduction of ASAQ in 2002-2003 (n = 208) and seven years after wide scale use of ASAQ in 2010 (n = 122). Results: There was a statistically significant decrease of pfcrt 76T (96-63%), pfmdr1 86Y (75-52%), 184Y (83-72%), 1246Y (28-16%) and the most common haplotypes pfcrt/pfmdr1 TYYD (46-26%) and TYYY (17-8%), while an increase of pfcrt/pfmdr1 KNFD (0.4-14%) and KNYD (1-12%). Conclusions: This is the first observation of a decreased prevalence of pfcrt 76T, pfmdr1 86Y, 184Y and 1246Y in an African setting after several years of extensive ASAQ use as first-line treatment for uncomplicated malaria. This may support sustained efficacy of ASAQ on Zanzibar, although it was unexpected considering that all these SNPs have previously been associated with amodiaquine resistance. The underlying factors of these results are unclear. Genetic dilution by imported P. falciparum parasites from mainland Tanzania, a de-selection by artesunate per se and/or an associated fitness cost might represent contributing factors. More detailed studies on temporal trends of molecular markers associated with amodiaquine resistance are required to improve the understanding of this observation.